On the prime number lemma of Selberg - Saidak, Filip (MATHEMATICA SCANDINAVICA, 2008)
The key result needed in almost all elementary proofs of the Prime Number Theorem is a prime number lemma proved by Atle Selberg in 1948. Without restricting ourselves to purely elementary techniques we show how the error term in Selberg’s fundamental lemma relates to the error term in the Prime Number Theorem. In spite of all the interest in this topic over the last sixty years this particular question seems to have been overlooked in the past.